2014
DOI: 10.1097/mnm.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Higher predictive value of tumour and node [18F]-FDG PET metabolic volume and TLG in advanced lung cancer under chemotherapy

Abstract: MV and TLG are powerful prognostic factors in advanced-stage lung adenocarcinoma being treated with chemotherapy. Focusing on the intrathoracic primary tumour increases the prognostic value of PET in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…In contrast to SUV max , TLG incorporates the metabolic burden and disease extent and may provide a higher predictive value. The results of our study revealed that whole-body tumor glycolysis represented by TLG WBR was a strong predictor of survival, which was similar to previously reported findings [ 18 , 23 24 ]. However, our study indicated that total glycolysis in the primary tumor alone (TLG T ) was not an independent predictor of survival, in line with some recent studies [ 19 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to SUV max , TLG incorporates the metabolic burden and disease extent and may provide a higher predictive value. The results of our study revealed that whole-body tumor glycolysis represented by TLG WBR was a strong predictor of survival, which was similar to previously reported findings [ 18 , 23 24 ]. However, our study indicated that total glycolysis in the primary tumor alone (TLG T ) was not an independent predictor of survival, in line with some recent studies [ 19 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the correlation between the PET/CT metabolic parameters (SUV max , primary TLG, and whole-body TLG) and survival in patients with advanced NSCLC, there has been some disagreement among researchers. Some studies have reported that whole-body TLG is a better prognostic predictor of worse OS and PFS in patients with advanced NSCLC [ 23 24 ], whereas other studies have found no such correlation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, it should be noted that the prognostic significance of TLG RECIST found in our study was limited to patients without EGFR mutations. The low frequency of EGFR mutations in whites 5 may explain the comparable findings.…”
Section: Discussionmentioning
confidence: 62%
“…For quantitation, we assessed [ 18 F]FHBG total activity within the generated ROI (SUV mean × volume of interest) as an unbiased measure of [ 18 F]FHBG signal in a fixed volume region within the brain (namely the tumor) and in the setting where the [ 18 F]FHBG signal, and therefore CTLs, was widely dispersed after CTL infusions. This metric is comparable to total lesion glycolysis used with [ 18 F]2-fluoro-2-deoxy-D-glucose ([ 18 F]FDG) PET, which is a more sensitive marker than SUV max or SUV mean for the evaluation of therapeutic response and prognosis (4446). …”
Section: Discussionmentioning
confidence: 97%